Intraoperative Neuromonitoring: Evaluating the Role of Continuous IONM and IONM Techniques for Emerging Surgical and Percutaneous Procedures - McManus, Catherine; Kuo, Jennifer Hong (Frontiers in Endocrinology, 2022)
Intraoperative nerve monitoring (IONM) is a tool used during thyroid surgery to assist in the identification of the recurrent laryngeal nerve (RLN). Multiple IONM systems that exist for thyroidectomy require intubation with an endotracheal tube. Given that one of the advantages of thermal ablation procedures, such as radiofrequency ablation, is that they can be done safely without the use of general anesthesia, nerve monitoring systems that utilize cutaneous surface electrodes have been developed. This article will review the use of IONM for RFA including the cutaneous surface electrode system.